Tourist Product — Place - Stasiak, Andrzej; Włodarczyk, Bogdan (Turyzm/Tourism, 2003)
Among numerous territorial products one can name the tourist product. The authors attempt to describe it, pointing out its lack of unity as a concept compared to the tourist product-place which functions in accordance with a certain higher order idea. The geographic determination of this type of product enabled the authors to try and describe the spatial relation between the tourist product-place and the tourist region.